Chemical Composition and Antioxidant Activity of the Main Fruits Consumed in the Western Coastal Region of Ecuador as a Source of Health-Promoting Compounds - Mabel Guevara; Eduardo Tejera; María G. Granda-Albuja; Gabriel Iturralde; Maribel Chisaguano-Tonato; Silvana Granda-Albuja; Tatiana Jaramillo-Vivanco; Francesca Giampieri; Maurizio Battino; José M. Alvarez-Suarez (MDPI AG, 2019)
We studied 19 different tropical fruits traditionally consumed in the coastal lowlands of Ecuador to determine their chemical composition and antioxidant activity. Carambola (Averrhoa carambola L.) had the highest total phenolic, flavonoid, and total antioxidant capacity values, whereas guava fruits (Psidium guajava L.) had the highest vitamin C values. The main organic acids identified were lactic, citric, and acetic acids, and the highest amount of lactic acid was found in soursop fruits (Annona muricata L.), whereas Ecuadorian ivory palm (Phytelephas aequatorialis Spruce) and guava fruits had the highest acetic acid content. Guava also had the highest citric acid content; the highest concentration of oxalic acid was found in carambola. In terms of sugar content, giant granadilla (Passiflora quadrangularis L.) had the highest values of glucose, and red mombin (Spondias mombin L.) had the largest values for fructose and guava for sucrose. Chili pepper (Capsicum chinense Jacq) proved to be the main source of carotenoids, lutein, and β-carotene, anthocyanins, and vitamin C. The results here increase our knowledge regarding the composition of the main fruits consumed on the west coast of Ecuador to facilitate recommendations as potential sources of health-promoting compounds.